Phylogenetic analysis of the Taeniothrips genus-group, with revision of the species of Ctenothrips and Vulgatothrips (Thysanoptera, Thripinae) - Wang, Zhaohong; Li, Yajin; Tong, Xiaoli; Mound, Laurence (Zootaxa, 2020)
The pattern of relationships within the Taeniothrips genus-group was examined using a morphological phylogenetic analysis. Genera comprising this group are discussed together with some character states used in the analysis. Taeniothrips genus-group is recovered as monophyletic, but Taeniothrips appears to be polyphyletic. Ctenothrips is here interpreted as sister-group to Vulgatothrips, with Ctenothrips smilax and C. dissimilis transferred to Vulgatothrips, and C. niger synonymized with C. smilax. Diagnoses of Ctenothrips and Vulgatothrips are presented with illustrated keys to distinguish these genera and their included species, and eight species are newly synonymised in Ctenothrips.